Where the conflict really lies: science, religion, and naturalism - Plantinga, Alvin (Oxford University Press, 2011)
Evolution and Christian belief (1) -- Evolution and Christian belief (2) -- Divine action in the world : the old picture -- The new picture -- Evolutionary psychology and scripture scholarship -- Defeaters? -- Fine-tuning -- Design discourse -- Deep concord : Christian theism and the deep roots of science -- The evolutionary argument against naturalism